Use of General Anesthesia in Pediatric Dental Treatment - Gasanaga, Mehmani Ilham; Rasim, Mehmani Vusala; Sergey, Ashrafov Davud (American Journal of Biology and Natural Sciences, 2026)
The highest degree of fear—dentophobia—can develop in childhood and persist throughout life. Emotional stress experienced during a dental visit leads to changes in physiological and biochemical processes in the body, which may result in psychovegetative disorders such as tachycardia, arterial hypertension, syncope, collapse, or psychogenic shock.